Renormalization group in potential scattering - Adhikari, Sadhan K. [UNESP]; Frederico, T. [UNESP] (American Physical Society (APS), 1995)
Renormalization group equations for the physical t matrix are written for quantum scattering with some potentials singular at the origin in two and three dimensions. The momentum-space perturbative treatment of these scattering problems exhibits ultraviolet divergences and permits renormalization leading to a scale. These equations yield the correct asymptotic behavior and some low-energy properties of the t matrix. Illustrations are made for the Dirac delta potential in two and three dimensions. © 1995 The American Physical Society.